TREATMENT FOR ACUTE INTOXICATIONS WITH VENOMS: COBRA SNAKEBITES - G. A. Livanov; B. V. Batotsyrenov; A. N. Lodyagin; A. Yu. Andrianov; O. A. Kuznetsov; D. V. Baranov; I. V. Nezhentseva (Общая реаниматология, 2015)
Objective: to study the specific features of the clinical course of acute intoxications with venoms due to the bites of Naja (cobra) naja and Naja kaouthia and those of intensive therapy in patients with the severest forms of this condition. Subjects and methods. Two clinical cases of acute intoxications with venoms due to Naja naja and Naja kaouthia bites were examined. The specific features of their clinical picture over time, changes in clinical and biochemical indicators, blood gas composition, and acidbase balance, coagulogram readings, ECG and radiological findings were studied. Results. Acute intoxication with venoms due to serious cobrabites was found to be characterized by the development of toxicohypoxic encephalopathy, toxic myopathy with skeletal and respiratory muscle paresis to develop acute respiratory and cardiovascular failure, coagulopathy, and metabolic disorders. Specific therapy (with an anti-ophidic serum in one case) resulted in drastically worsening health conditions as fulminant acute respiratory distress syndrome. A package of intensive therapy measures should include actions based on general resuscitation approaches — maintenance of life support systems (breathing, blood circulation), anti-sensitizing therapy, correction of metabolic disturbances with substrate antihypoxants (cytofavin, reamberin), and antimicrobial therapy. Conclusion. In the severest acute intoxications due to cobra snakebites, specific therapy methods (with anti-ophidic serum) should be used with extreme caution and particular emphasis should be laid on the general resuscitation-based principles.